Tahlilul bi Naud As’ilah al-Tadribat li Shaf al-Tsani al-Mutawashit fi Kitab Ta’lim al-Lughah al-‘Arabiyyah li Wizarah al-Syu’un al-Diniyyah al-Indunisiyyah ‘Am 2022 - Miftahusa’adah, Miftahusa’adah; Isman, Nofa; Nuradi, Nuradi; Mufarokah, Siti; Gazali, Zuhdina (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
Good exercises affect the quality of the textbook. This study aims to describe the types of exercises (mechanism / patterns, meaning, communication) in the Arabic language teaching book for the second intermediate grade of the Ministry of Religious Affairs in 2020 AD, and to describe the types and form of the questions of the exercises, and to describe the exercises of four language skills and three language elements in it. This study follows the descriptive approach with a qualitative approach. The results revealed that the exercises in this book included patterns, meaning, and communication exercises, and also included 17 forms of questions. As for the exercises for language skills and language elements, there were no exercises for listening skill or sounds exercises in this book. With this comprehensiveness, the exercises in this book are considered good and valid for measuring students' abilities.